Miniatures, morphology and molecules: Paedocypris and its phylogenetic position (Teleostei, Cypriniformes). (8th October 2014) - Britz, Ralf; Conway, Kevin W.; Rüber, Lukas
<x xml:space="preserve">Abstract</x> We review the morphological and molecular evidence that Mayden & Chen recently used to infer that the developmentally truncated fish genus Paedocypris is not a member of the teleost order Cypriniformes or carp‐like fishes, but is 'the basal sister group to all Cypriniformes'. This hypothesis contradicts several previous studies that used molecular sequence data or morphological characters. A review of the morphological characters that Mayden & Chen discussed and mapped onto their 'simplified tree' shows that these, analysed alone, rather support a close relationship of the cyprinids Sundadanio, Danionella, and Paedocypris. We also present four additional analyses of morphological data, which all contradict Mayden & Chen's result. Despite its highly reductive skeleton, posing a serious problem when analysing its phylogenetic position with skeletal characters, the presence in Paedocypris of the basioccipital masticatory plate is compelling evidence that it is a member of the Cyprinoidei (Cyprinidae plus Psilorhynchidae). Our reanalysis and exploration of their molecular sequence data shows that only a single gene, EGR3, of the six nuclear genes analysed by Mayden & Chen, is responsible for the position of Paedocypris as 'the basal sister group to all Cypriniformes'. Three independent methods to visualize and analyse phylogenetic signal and conflict of data sets (phylogenetic networks, splits analysis methods or SAMS, and site‐wise likelihood analyses) reveal a high level of character conflict and noise in Mayden & Chen's data set. The 'basal' position of Paedocypris seems to be the outcome of the interplay of two long‐branch effects. We apply the same analytical methods to the data set from Rüber et al.'s molecular analysis of the phylogenetic position of Paedocypris and discuss our findings. We conclude that none of the molecular data sets compiled to date can establish the phylogenetic position of Paedocypris with confidence. Morphological data suggest that Paedocypris and Danionella are sister genera, and that their closest relative is Sundadanio, although the position of these three miniatures among cyprinoids is still unclear. © 2014 The Linnean Society of London